War and Memorials The Age of Nationalism and the Great War. - Jacob, Frank (War (Hi) Stories Ser., 2019)
War Memorials were an important element of nation building, for the invention of traditions, and the establishment of historical traditions. Especially nationalist remembrance in the late 19th century and the memory of the First World War stimulated a memorial boom in the period which the present book is focusing on. The remembrance of war is nothing particularly new in history, since victories in decisive battles had been of interest since ancient times. However, the age of nationalism and the First World War triggered a new level of war remembrance that was expressed in countless memorials all over the world. The present volume presents the research of international specialists from different disciplines within the Humanities, whose research is dealing with the role of war memorials for the remembrance of conflicts like the First World War and their perceptions within the analyzed societies. It will be shown how memorials - in several different chronological and geographical contexts - were used to remember the dead, remind the survivors, and warn the descendants.